Day 3 Wed, March 08, 2017 2017
DOI: 10.2118/183737-ms
|View full text |Cite
|
Sign up to set email alerts
|

Gravel Pack a 500 ft High Permeability Cased Hole Well: Case Study, Gulf of Suez, Egypt

Abstract: Sand production has always been a challenge for oil operators worldwide. Several parameters can lead to sand production, including poor cementing material in the reservoir, high production rates, and high drawdown applied to an unstable zone. The subject field consists of 105 wells; 90 of these wells are oil producing wells, 11 are water injection wells, two are dump flood wells, and two are water source wells. The primary challenge was to perform a gravel pack job on a high permeability water source well to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…The productivity of a gravel-packed well depends on the permeability of the gravel-pack sand and how it is placed. To ensure maximum well productivity, one should use high-quality gravel-pack sand (Khaled et al, 2017). The analysis of the productivity of cased-hole and openhole gravel packs (Penberthy and Cope, 1980) has shown that cased-hole gravel packs result in well productivities far below the productivity of open-hole packs while maintaining the significance of perforation diameter and sot density.…”
Section: Introductionmentioning
confidence: 99%
“…The productivity of a gravel-packed well depends on the permeability of the gravel-pack sand and how it is placed. To ensure maximum well productivity, one should use high-quality gravel-pack sand (Khaled et al, 2017). The analysis of the productivity of cased-hole and openhole gravel packs (Penberthy and Cope, 1980) has shown that cased-hole gravel packs result in well productivities far below the productivity of open-hole packs while maintaining the significance of perforation diameter and sot density.…”
Section: Introductionmentioning
confidence: 99%